PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA MELALUI PELATIHAN DASAR-DASAR MANAJEMEN DAN ANALISIS SWOT PADA SEKTOR PERTANIAN TEMBAKAU DI KABUPATEN SUMEDANG - Rejito, Cattleya; Dewi, Adifa Putri; Fachrilla, Virsahaya (STAI Darul Qalam Tangerang, 2023)
Human resources have become one of the essential aspects in the industrial business sector, including the tobacco agriculture sector that involves various stakeholders. The training provided to tobacco agriculture entrepreneurs in the Sumedang Regency aims to equip them with fundamental managerial skills and the ability to analyze both external and internal environments using SWOT analysis. Through this training, participants are expected to focus more on their businesses, leading to more effective and efficient management. Additionally, entrepreneurs are encouraged to take strategic steps in the future based on SWOT analysis principles. The training took place in Sumedang Regency and involved approximately 60 participants. As a result of this training, participants were able to apply fundamental management principles and create simple SWOT analyses relevant to the tobacco agriculture sector